Surface co-modification of TiO2 with N doping and Ag loading for enhanced visible-light photoactivity. Issue 15 (1st February 2016) - Sun, Mingxuan; Fang, Yalin; Sun, Shanfu; Wang, Ying
Abstract : A composite of N-doped TiO2 with Ag loading (Ag/N-TiO2 ) was successfully synthesized by a facile in situ calcination process using titanium nitride (TiN) and silver nitrate (AgNO3 ) as the starting materials. Abstract : A composite of N-doped TiO2 with Ag loading (Ag/N-TiO2 ) was successfully synthesized by a facile in situ calcination process using titanium nitride (TiN) and silver nitrate (AgNO3 ) as the starting materials. The effects of Ag loading and N doping on the structure and properties of TiO2 were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and diffuse reflectance spectroscopy (UV-visible DRS). XPS results indicated that the loading content of Ag in Ag/N-TiO2 nanomaterials can be adjusted by varying the amount of AgNO3 in the starting materials. There is an enhanced light absorption and a red shift of the optical edge for the resulting Ag/N-TiO2 compared with bare TiO2 and N-doped TiO2 . The photocatalytic activities of the samples were evaluated for the degradation of methylene blue in aqueous solutions under visible light ( λ > 420 nm). The superior visible light photodegradation of Ag/N-TiO2 composites was confirmed compared to N-doped TiO2 nanoparticles. In addition, an enhanced visible light photoelectrochemical performance was demonstrated. The photocurrent and photovoltage of Ag/N-TiO2 were about 1.5 and 1.4 times larger than those of N-TiO2, respectively. The technique proposed in this paper can also be applied to fabricate other N-TiO2 based composites.